Confidence Index Analysis of Twitter Users Timeline - Is, Hafzullah; Tuncer, Taner (Ieee, 2018)
With the development of information technologies and the increase of means and facilities for accessing the internet, the number of users of popular social networks has started to increase rapidly. Twitter is the most requested microblog site with 336 million active users. On Twitter, users can instantly express ideas, emotions and reactions with tweets. Scalable data from microblog sites, where fast and effective responses can be obtained, can be used in political, social and economic areas. It is possible to analyze the characteristics, trends and behaviors of the users by revealing their interaction. In recent years, especially the emotional analysis of users has become very popular. By analyzing the characters, effects and trends of users in Twitter, business intelligence applications can be developed and individual and social strategies can be created. In this study, the Twitter profiles of Turkey presidential election candidate were examined. Profiles was measured by physical and emotional metrics such as density, reciprocity, centralization, modularity, polarity, subjectivity. Users profiles confidence level and social authority indexes was determined. Relations with each other have been revealed. By examining these metrics, the effects of social media usage habits on users' followers are examined. Social media performances were measured from each candidate's tweets and follower analysis. Confidence indices related to 6-week time series were extracted using hierarchical classification algorithm.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Social Media; Twitter; Quality Scaling Criteria; Semantic Analysis; Hierarchical Classification; Time Series